Ancymidol blocks trichothecene biosynthesis and leads to accumulation of trichodiene in Fusarium sporotrichioides and Gibberella pulicaris. - Desjardins, A E (1987)
Ancymidol, a plant growth regulator, inhibited biosynthesis of diacetoxyscirpenol by Gibberella pulicaris (Fusarium sambucinum) in a defined liquid medium. Ancymidol also inhibited biosynthesis of T-2 toxin by a wild-type strain of Fusarium sporotrichioides and biosynthesis of diacetoxyscirpenol, deacetylated calonectrin, and dideacetylated calonectrin by mutant strains of this species. Ancymidol-treated cultures accumulated the hydrocarbon trichodiene, a biosynthetic precursor of the trichothecenes. Ancymidol did not block trichodiene accumulation by a trichodiene-producing mutant strain of F. sporotrichioides. Ancymidol appears to block the trichothecene biosynthetic pathway after formation of trichodiene and before formation of trichothecenes containing four or more oxygen atoms.